2004
DOI: 10.1103/physrevb.70.104428
|View full text |Cite
|
Sign up to set email alerts
|

Dilution of two-dimensional antiferromagnetism by Mn site substitution inLa1Sr2Mn2xAlx<

Abstract: We report the effect of Al substitution on the Mn site of the bilayered half doped manganite La1Sr2Mn2O7. This substitution dilutes the magnetically active Mn-O-Mn network without introducing an appreciable distortion in the lattice and ionic considerations leads to a predominant reduction of Mn 4+ with increasing Al. The rate of fall of the long range antiferromagnetic transition temperature as a function of substitution is seen to match well with established quasi 2D Heisenberg systems indicating that the na… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…The initial suppression rate for T H of 2.2 is somewhat larger than the expected values for 2D Ising spins, which are generally in the range of 1.6-1.9, although it is smaller than typical values for 2D Heisenberg spins (approximately 3) [21]. The initial suppression rate for T L (4.3) is larger even that computed for 2D Heisenberg spins (% 3), although it is roughly consistent with that observed in other systems, including La 2 CuO 4 doped with Mg and Zn [21] and Al doped LaSr 2 Mn 2 O 7 [24]. These dilution studies suggest that the HTI phase acts like a 2D Ising spin system, while the LTI phase acts like a 2D Heisenberg spin system.…”
Section: Effects Of Zn Dopingsupporting
confidence: 77%
“…The initial suppression rate for T H of 2.2 is somewhat larger than the expected values for 2D Ising spins, which are generally in the range of 1.6-1.9, although it is smaller than typical values for 2D Heisenberg spins (approximately 3) [21]. The initial suppression rate for T L (4.3) is larger even that computed for 2D Heisenberg spins (% 3), although it is roughly consistent with that observed in other systems, including La 2 CuO 4 doped with Mg and Zn [21] and Al doped LaSr 2 Mn 2 O 7 [24]. These dilution studies suggest that the HTI phase acts like a 2D Ising spin system, while the LTI phase acts like a 2D Heisenberg spin system.…”
Section: Effects Of Zn Dopingsupporting
confidence: 77%
“…The calculated results for lattice parameters are collected in Table 2. The lattice parameters are in good agreement with the earlier studies [24][25][26]. A monotonic incensement trend was seen in the a-lattice parameter and the unit cell volume of samples (Fig.…”
Section: Resultssupporting
confidence: 90%
“…The decreasing value of N(E F ) with the decrease of the size of lanthanide ion also indicates that the ability to conduct decreases from LSMO to SSMO. The obtained best fit parameters are in good agreement with the previous reports on similar DL manganites [21,[29][30][31][32]36]. All the fitting parameters in Mott 2D and 3D VRH models vary in a similar manner with lanthanide ion and these results suggest the reliability of the performed fittings.…”
Section: Electrical Resistivity and Conduction Mechanism At T > T Imsupporting
confidence: 80%
“…In case of DL manganites, the conduction at T > T IM has been explained by Matsukawa et al [29], Zhu et al [30] and others [21,31,32] using Mott type VRH while Chatterjee et al [12] and others [33,34] suggested SPH model. Chen et al [35] suggested ES VRH type of conduction in similar DL manganites.…”
Section: Electrical Resistivity and Conduction Mechanism At T > T Immentioning
confidence: 99%